Crosstalk Between Mesenchymal Stromal Cells and Tumor-Associated Macrophages in Gastric Cancer - Zheng, Ping; Li, Wei (Frontiers in Oncology, 2020)
Tumor microenvironment (TME) consisting of distinct cell types including stromal cells and immune cells, has recently emerged as a pivotal player in tumor development and progression. Mesenchymal stromal cells (MSCs) and tumor-associated macrophages (TAMs) are two representative cells in the TME with plastic properties. This review will be focus on the evolution of phenotypes and functions of either MSCs or TAMs, which is ‘educated’ by the TME, as well as interactions between MSCs and TAMs contributing to the distinct stages of tumor development and progression in gastric cancer. MSCs exert immunoregulatory effect on macrophages and polarized them toward M2-like TAMs, via cell-cell contact, paracrine or extracellular vesicles (EVs) transfer mechanism. In turn, M2-TAMs modulate the transition of “naive” MSCs into tumor-derived MSCs, which possess a more potent pro-tumor role than the parent. Moreover, the crosstalk between MSCs and TAMs could contribute to cancer biology by induce the EMT process, metastasis, immune invasion and immunotherapy resistance in cancer cells. However, molecular mechanisms underlying interactions between MSCs and TAMs in the gastric cancer progression need to be thoroughly elucidated, which may provide attractive targets for making promising novel strategies for gastric cancer therapy.